Pengaruh Supporting Electrolyte pada Penentuan Formaldehida secara Voltametri Siklik Menggunakan Au/MWCNT/GCE - Annisa, Ananda Suci; Sari, Trisna Kumala; Dewata, Indang; Khair, Miftahul; Suryani, Okta (Departemen Kimia FMIPA UNP, 2024)
Formaldehyde was detected electrochemically using a modified glassy carbon electrode with a multi-walled carbon nanotube (MWCNT) and a thin layer of gold (Au). Modification of MWCNT was carried out by drop coating, while modification of the thin layer of gold was carried out by sweeping-potential electrodeposition using the cyclic voltammetry method. The purpose of this study was to develop a formaldehyde sensor using Au/MWCNT/GCE and to determine the optimum conditions of the supporting electrolyte for formaldehyde measurement. The results showed that Au/MWCNT/GCE provided better catalytic activity than GCE, MWCNT/GCE and Au/GCE electrodes in the determination of formaldehyde. The optimum supporting electrolyte obtained was KOH with a test analyte concentration of 10 mM. The oxidation peak of formaldehyde I is at a potential of 0.0264 V and peak of oxidation of formaldehyde II is at a potential of 0.075 V.